Integrative study reveals the prognostic and immunotherapeutic value of CD274 and PDCD1LG2 in pan-cancer - Zhou, Xuan; Wang, Yu; Zheng, Jianwei; Wang, Sinan; Liu, Chao; Yao, Xiaofeng; Ren, Yu; Wang, Xudong (Frontiers in Genetics, 2022)
Abstract Background Disorders of CD274 and PDCD1LG2 contribute to immune escape in human cancers, and treatment with anti-programmed death receptor 1 (PD-1) has been widely used in recurrent or metastatic tumors. However, integrated studies considering CD274 and PDCD1LG2 across cancers remain limited. Materials and Methods Differences in expression levels of CD274 and PDCD1LG2 were analyzed in diverse cancer types using The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases. The clinical information and matched expression profiles of TCGA patients were obtained to determine the prognostic value of CD274 and PDCD1LG2. Moreover, correlations between CD274 and PDCD1LG2 and the immune signature were analyzed by exploring the TIMER2 and TISIDB databases. We also investigated correlations between CD274 and PDCD1LG2 and immunotherapeutic biomarkers, including mismatch repair (MMR), tumor mutation burden (TMB), microsatellite instability (MSI), and DNA methylation. Results Expression levels of CD274 and PDCD1LG2 varied across multiple cancer types. CD274 and PDCD1LG2 not only impacted the prognosis of patients with cancer but were associated with clinical characteristics (lymph node metastasis, tumor stage, and sex) in kidney renal papillary cell carcinoma, thyroid carcinoma, and some other cancer types. Typically, CD274 and PDCD1LG2 could be strongly correlated with macrophages, dendritic cells, neutrophils, and CD8+ T-cells. Furthermore, CD274 and PDCD1LG2 expression were associated with various immunosuppressive biomarkers, such as CTLA4, TIGIT, and LAG3. In addition, CD274 and PDCD1LG2 were significantly associated with MMR, TMB, MSI, and DNA methylation. Finally, enrichment analysis confirmed that CD274 and PDCD1LG2 were associated with numerous biological pathways, such as: “Activation of Immune Reactions” and “Epithelial-Mesenchymal Transition,” suggesting that CD274 and PDCD1LG2 play crucial roles in cancer immunity and tumor metastasis. Conclusion CD274 and PDCD1LG2 play critical roles in cancer progression and immune response and could serve as effective biomarkers to predict the prognosis and immune signature of cancer.